Occupational Chromium Allergy and Contact Dermatitis: 10 Years Evolution - Afonso,Alexandre (2021)
ABSTRACT Introduction: Chromium has been responsible for occupational skin disease, both irritant and/or allergic contact dermatitis. In order to minimize this problem, regulatory measures limiting its use have been implemented. The impact of these regulations should be monitored over time. Material and Methods: A retrospective study from 2009 to 2018 was carried out in the Department of Dermatology to assess the temporal trend of chromium sensitization evaluated by patch testing with potassium dichromate 0.5% pet, particularly considering age, sex and its relationship with occupational activity. Results: 3277 individuals were studied, 2369 females (72.29%) and 908 males (27.71%). Of those 621 (18.95%) fulfilled criteria for occupational contact dermatitis. Chromium allergy was found in 118 (3.60%) patients, 64 females (54.4%) and 54 males (45.76%). We found that male patients were significantly more frequent (45.76% vs 27.03%; p<0.001), as well as occupational dermatitis (31.35% vs 18.47%; p<0.001), hand dermatitis (53.54% vs 23.52%; p<0.001) and age above 40 years (70.34% vs 56.76%; p=0.003). Discussion/Conclusion: The results show a high prevalence (3.60%) of chromium positive patch tests. In our study, there has not been a significant decrease in sensitization to chromium over the years. Interestingly cases classically related to this allergy (cement in the building industry) are no longer the main cause of the problem. We found other sources such as leather as a main cause of allergic sensitization, suggesting a change of the panorama.